2009
DOI: 10.1128/jcm.00766-09
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Real-Time PCR for Rapid Staphylococcal Cassette Chromosome mec Typing

Abstract: Rapid identification and typing of methicillin (meticillin)-resistant Staphylococcus aureus (MRSA) is important for understanding the molecular epidemiology and evolution of MRSA and offers many advantages for controlling transmission in both health care and community settings. We developed a rapid molecular beacon real-time PCR (MB-PCR) assay for staphylococcal cassette chromosome mec (SCCmec) typing. The design of this system is based on the established definition of SCCmec types, namely, the combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 83 publications
(111 reference statements)
1
68
0
Order By: Relevance
“…Methicillin resistance in Staphylococcus aureus (MRSA) in humans as well as in foods of animal origin and its prevalence has been increasing worldwide. This resistance is due to the acquisition of genes encoding a unique penicillin-binding protein (PBP2'or PBP2a) (Chen et al, 2009). Studies in different countries have strongly suggested that consumption of under cooked MRSA contaminated meat could be responsible for the prevalence of MRSA in the community (Ogata et al, 2102).…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2459-2466mentioning
confidence: 99%
“…Methicillin resistance in Staphylococcus aureus (MRSA) in humans as well as in foods of animal origin and its prevalence has been increasing worldwide. This resistance is due to the acquisition of genes encoding a unique penicillin-binding protein (PBP2'or PBP2a) (Chen et al, 2009). Studies in different countries have strongly suggested that consumption of under cooked MRSA contaminated meat could be responsible for the prevalence of MRSA in the community (Ogata et al, 2102).…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2459-2466mentioning
confidence: 99%
“…Methicillin resistance was determined using standard laboratory techniques and SCCmec typing performed as previously described. 28 Serology assay. A direct binding assay was developed for the detection of total IgG antibodies to IsdB, using Luminex ® technology.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Four fungal strains (Candida albicans) were also included. All bacterial and fungal strains were selected from our previous studies (1,17). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, agr functionality among 269 single-patient MRSA isolates was determined by screening for synergistic and direct hemolysis (15). All 269 isolates were previously genotyped by a combination of methods, including spa typing, SCCmec typing, and pulsed-field gel electrophoresis (PFGE) (1,10,16). Although the majority of strains were deemed positive for ␦-hemolysin production (synergistic hemolysis), 40 strains were identified as nonhemolytic, while 13 exhibited a mixture of both hemolytic and nonhemolytic colonies (15).…”
mentioning
confidence: 99%